Employee attitudes as a mediator between HRM and organizational performance - Ali Akeel, Mohamed Elfadeel; Omar, Roshartini; Masrom, M. A .N. (AENSI Publications, 2018)
Attitude is a power that controls human behaviour. When employee Attitude is positive, it can give impact positive to organization performance. A proper human resource management (HRM) managed by organization, the employee attitude will be affected. HRM practices influence employee attitude positively and there is a mediating role of employee attitude between training and development dimension of HRM practices and organizational performance. Therefore, the purpose of this study is to explore employee atttiude as a mediator between HRM and organizational performance. A sample of this study was 219 respondents from employee construction in Libya. The data was analyzed using structural equation modelling (SEM) approach. This study showed that employee attitudes is a full mediator between relationship HRM and organizational performance. Therefore, HRM practices influence employee attitude and its give impact to organizational performance for more effective and efficient in achieving organization goal.